Access to a Labile Monomeric Magnesium Radical by Ball-Milling - Jedrzkiewicz, Dawid; Mai, Jonathan; Langer, Jens; Mathe, Zachary; Patel, Neha; DeBeer, Serena; Harder, Sjoerd (Angewandte Chemie International Edition, 2022)
In order to isolate a monometallic Mg radical, the precursor (Am)MgI⋅(CAAC) (1) was prepared (Am=tBuC(N-DIPP)2, DIPP=2,6-diisopropylphenyl, CAAC=cyclic (alkyl)(amino)carbene). Reduction of a solution of 1 in toluene with the reducing agent K/KI led to formation of a deep purple complex that rapidly decomposed. Ball-milling of 1 with K/KI gave the low-valent MgI complex (Am)Mg⋅(CAAC) (2) which after rapid extraction with pentane and crystallization was isolated in 15 % yield. Although a benzene solution of 2 decomposes rapidly to give Mg(Am)2 (3) and unidentified products, the radical is stable in the solid state. Its crystal structure shows planar trigonal coordination at Mg. The extremely short Mg−C distance of 2.056(2) Å indicates strong Mg−CAAC bonding. Calculations and EPR measurements show that most of the spin density is in a π* orbital located at the C−N bond in CAAC, leading to significant C−N bond elongation. This is supported by calculated NPA charges in 2: Mg +1.73, CAAC −0.82. Similar metal-to-CAAC charge transfer was calculated for M0(CAAC)2 and [MI(CAAC)2+] (M=Be, Mg, Ca) complexes in which the metal charges range from +1.50 to +1.70. Although the spin density of the radical is mainly located at the CAAC ligand, complex 2 reacts as a low-valent MgI complex: reaction with a I2 solution in toluene gave (Am)MgI⋅(CAAC) (1) as the major product.
CRIS-Team Scopus Importer:2022-02-25
Keywords: DFT Calculations; EPRSpectroscopy; Low-Valent Complexes; Magnesium; Radicals

Alkali metal influences in aluminyl complexes - Grams, Samuel; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (Dalton Transactions, 2022)
The previously reported potassium aluminyl complex [(BDI-H)Al−K+]2 was converted in Li+ or Na+ salts by a salt metathesis reaction with Li(BPh4) or Na(BPh4), respectively; BDI-H = dianionic [(DIPP)N-C(Me) 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 C(H)-C( CH2)-N(DIPP)2−] and DIPP = 2,6-diisopropylphenyl. The Rb and Cs aluminyl complexes were obtained by reaction of (BDI)Al with RbC8 or CsC8; BDI = HC[C(Me)N(DIPP)]2. Crystal structures of two monomers, (BDI-H)Al−Li+·(Et2O)2 and (BDI-H)Al−Na+·(Et2O)(TMEDA), and four dimers [(BDI-H)Al−M+]2 (M = Li, Na, Rb, Cs) are discussed. Lewis base-free dimers [(BDI-H)Al−M+]2 crystallize either as slipped dimers (Li+, Na+) in which each Al center features only one Al-M contact or as a symmetric dimer (K+, Rb+, Cs+) in which the cation bridges both Al centers. The dimer with the largest cation (Cs+) shows Cs⋯CH2 C interactions between dimers, resulting in a coordination polymer. AIM and charge analysis reveal highly ionic Al-M bonds with strong polarization of the Al lone-pair towards the smaller cation Li+ and Na+. The Al-M bonds become weaker from Li to Cs. Calculated dimerization energies suggest that in apolar solvents only complexes with the heavier metals Rb and Cs may be in a monomer-dimer equilibrium. This is confirmed by DOSY measurements in benzene. Dimeric aluminyl complexes with heavier alkali metals (K-Cs) react with benzene to give a double C-H activation in para-positions.
CRIS-Team Scopus Importer:2022-08-12

Alkaline-Earth Metal Mediated Benzene-to-Biphenyl Coupling - Mai, Jonathan; Morasch, Michael; Jedrzkiewicz, Dawid; Langer, Jens; Rösch, Bastian; Harder, Sjoerd (Angewandte Chemie International Edition, 2022)
Complex [(DIPePBDI)Ca]2(C6H6), with a C6H62− dianion bridging two Ca2+ ions, reacts with benzene to yield [(DIPePBDI)Ca]2(biphenyl) with a bridging biphenyl2− dianion (DIPePBDI=HC[C(Me)N-DIPeP]2; DIPeP=2,6-CH(Et)2-phenyl). The biphenyl complex was also prepared by reacting [(DIPePBDI)Ca]2(C6H6) with biphenyl or by reduction of [(DIPePBDI)CaI]2 with KC8 in presence of biphenyl. Benzene-benzene coupling was also observed when the deep purple product of ball-milling [(DIPPBDI)CaI(THF)]2 with K/KI was extracted with benzene (DIPP=2,6-CH(Me)2-phenyl) giving crystalline [(DIPPBDI)Ca(THF)]2(biphenyl) (52 % yield). Reduction of [(DIPePBDI)SrI]2 with KC8 gave highly labile [(DIPePBDI)Sr]2(C6H6) as a black powder (61 % yield) which reacts rapidly and selectively with benzene to [(DIPePBDI)Sr]2(biphenyl). DFT calculations show that the most likely route for biphenyl formation is a pathway in which the C6H62− dianion attacks neutral benzene. This is facilitated by metal-benzene coordination.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Alkaline-Earth Metal; Cross-Coupling; DFT Calculations; Low-Valent; Mechanochemistry

A Modular Approach to Asymmetric Mg(I) Complexes Using a Unique Cyclopentadienyl Mg(I) Complex - Stecher, Hannah; Thum, Stefan; Maurer, Johannes; Mai, Jonathan; Schmidt, Marcel; Langer, Jens; Harder, Sjoerd (Angewandte Chemie International Edition, 2025)
The first MgI complexes with non-N ligands have been isolated and were fully characterized. Reaction of [(BDI*)MgNa]2 (III) with MgCp*2 gave quantitative conversion to (BDI*)MgMgCp* (1); BDI* = HC[tBuC = N(DIPeP)]2, DIPeP = 2,6-Et2CH-phenyl) and Cp* = pentamethylcyclopentadienyl. A similar reaction with CaCp*2 did not give (BDI*)MgCaCp* but led to insertion of the formal Mg° centre in the benzylic C─H bond, an oxidative addition that resulted in a mixed Mg/Ca hydride complex. The Cp* ligand in the unique (BDI*)MgMgCp* complex can be exchanged by addition of LM (M = Li, Na, K) complexes, resulting in formation of (BDI*)MgMgL and insoluble (Cp*M)n. This modular approach worked for Cp*/N(SiMe3)2 exchange but not for the substitution of Cp* by P(SiMe3)2 or other PR2 ligands. Reaction of (BDI*)MgMgCp* with a bulky NaOAr reagent led to quantitative formation of (BDI*)MgMgOAr·THF, a first MgI complex stabilized with an aryloxide ligand. All products have been fully characterized by X-ray diffraction and NMR methods. A computational study gives insight in the thermodynamics of formation and electronic structures.
CRIS-Team Scopus Importer:2025-10-31
Keywords: Calcium; DFT; Ligand exchange; Low-valent; Magnesium

Application of a Stable and Soluble Dibenzylbarium Reagent in the Synthesis of a Barium Imido Cluster - Rösch, Bastian; Martin, Johannes; Eyselein, Jonathan; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Organometallics, 2021)
The complex (DMAT)2Ba·(THF)2 (DMAT = 2-dimethylamino-α-trimethylsilylbenzyl) was prepared by a salt metathesis reaction between (DMAT)K and BaI2 in THF, and crystals were isolated in 83% yield. This monomeric complex dissolves well in aromatic or ethereal solvents and is also stable at higher temperatures in solution. Structural details and NMR parameters reveal a high degree of charge delocalization in the DMAT aryl ring. Comparison with identical Ca and Sr complexes, (DMAT)2Ae·(THF)2 (Ae = Ca and Sr), shows that the extent of delocalization increases down group 2: Ca < Sr < Ba. Due to chirality at the benzylic carbon, in solution the heterochiral R,S-isomer and homochiral R,R/S,S-isomers exist in equilibrium. A temperature-dependent NMR study gives an estimate of the Ae-C and Ae-N bond energies which decrease down the group: Ca > Sr > Ba. Although the DMAT carbanion is stabilized by resonance and negative hyperconjugation, (DMAT)2Ba·(THF)2 is still a very potent deprotonation reagent. Double deprotonation of Ph3SiNH2 gave the first Ba imido complex. A similar reaction using (DMAT)2Sr·(THF)2 gave the analogue Sr imido complex. Comparison with reported structures shows trends for the full series [(Ph3SiN)Ae·(THF)]4 (Ae = Mg, Ca, Sr, and Ba) which crystallize as tetramers with very stable, ionically bound heterocubane Ae4N4 cores.
CRIS-Team Scopus Importer:2021-06-04

Boosting Low-Valent Aluminum(I) Reactivity with a Potassium Reagent - Grams, Samuel; Eyselein, Jonathan; Langer, Jens; Färber, Christian; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
The reagent RK [R=CH(SiMe3)2 or N(SiMe3)2] was expected to react with the low-valent (DIPPBDI)Al (DIPPBDI=HC[C(Me)N(DIPP)]2, DIPP=2,6-iPr-phenyl) to give [(DIPPBDI)AlR]−K+. However, deprotonation of the Me group in the ligand backbone was observed and [H2C=C(N-DIPP)−C(H)=C(Me)−N−DIPP]Al−K+ (1) crystallized as a bright-yellow product (73 %). Like most anionic AlI complexes, 1 forms a dimer in which formally negatively charged Al centers are bridged by K+ ions, showing strong K+⋅⋅⋅DIPP interactions. The rather short Al–K bonds [3.499(1)–3.588(1) Å] indicate tight bonding of the dimer. According to DOSY NMR analysis, 1 is dimeric in C6H6 and monomeric in THF, but slowly reacts with both solvents. In reaction with C6H6, two C−H bond activations are observed and a product with a para-phenylene moiety was exclusively isolated. DFT calculations confirm that the Al center in 1 is more reactive than that in (DIPPBDI)Al. Calculations show that both AlI and K+ work in concert and determines the reactivity of 1.
CRIS-Team Scopus Importer:2020-07-10
Keywords: aluminum; C−H activation; density-functional calculations; low-valent complexes; potassium

Calcium catalyzed enantioselective intramolecular alkene hydroamination with chiralC2-symmetric bis-amide ligands - Stegner, Philipp; Eyselein, Jonathan; Ballmann, Gerd; Langer, Jens; Schmidt, Jochen; Harder, Sjoerd (Dalton Transactions, 2021)
The chiral building block (R)-(+)-2,2′-diamino-1,1′-binaphthyl, (R)-BINAM, which is often used as backbone in privileged enantioselective catalysts, was converted to a series ofN-substituted proligandsR1-H2(R = CH2tBu, C(H)Ph2, PPh2, dibenzosuberane, 8-quinoline). After double deprotonation with strong Mg or Ca bases, a series of alkaline earth (Ae) metal catalystsR1-Ae·(THF)nwas obtained. Crystal structures of theseC2-symmetric catalysts have been analyzed by quadrant models which show that the ligands with C(H)Ph2, dibenzosuberane and 8-quinoline substituents should give the best steric discrimination for the enantioselective intramolecular alkene hydroamination (IAH) of the aminoalkenes H2C=CHCH2CR′2CH2NH2(CR′2= CPh2, CCy or CMe2). The dianionicR12−ligand inR1-Ae·(THF)nfunctions as reagent that deprotonates the aminoalkene substrate, while the monoanionic (R1-H)−ligand formed in this reaction functions as a chiral spectator ligand that controls the enantioselectivity of the ring closure reaction. Depending on the substituent R in the BINAM ligand, full cyclization of aminoalkenes to chiral pyrrolidine products as fast as 5 minutes was observed. Product analysis furnished enantioselectivities up to 57% ee, which marks the highest enantioselectivity reported for Ca catalyzed IAH. Higher selectivities are impeded by double protonation of theR12−ligand leading to complete loss of chiral information in the catalytically active species.
CRIS-Team Scopus Importer:2021-03-19

Carbon-Halogen Bond Activation with Powerful Heavy Alkaline Earth Metal Hydrides - Wiesinger, Michael; Rösch, Bastian; Knüpfer, Christian; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2021)
Reaction of [(DIPePBDI)SrH]2 with C6H5X (X=Cl, Br, I) led to hydride-halogenide exchange (DIPePBDI=HC[(Me)CN-2,6-(3-pentyl)phenyl]2). Conversion rates increase with increasing halogen size (F<Cl<Br<I). Reaction of [(DIPePBDI)SrH]2 with C6H5F was slow and ill-defined but addition of C6H4F2 gave smooth hydride-fluoride exchange. After addition of THF the full range of Sr halogenides was structurally characterized: [(DIPePBDI)SrX ⋅ THF]2 (X=F, Cl, Br, I). Mixtures of AeN“2 and PhSiH3 in situ formed less defined but more robust Ae metal hydride clusters (AexN”yHz, Ae=Ca, Sr, Ba and N“=N(SiMe3)2) which are able to hydrodefluorinate C6H5F. Conversion rates increase with increasing metal size (Ca<Sr<Ba). Also alkylfluorides (1-F-hexane, F-cyclohexane, 1-F-adamantane) could be converted but, due to solubility problems of the Ba species, the fastest conversion was found for Sr. These AeN”2/PhSiH3 mixtures also converted SF6 at room temperature to give undefined decomposition products. Addition of Me6Tren to a SrN“2/PhSiH3 led to crystallization of [Sr6N”2H9 ⋅ (Me6Tren)3+][SrN“3−]; Me6Tren=tris[2-(dimethylamino)ethyl]amine). After hydrodefluorination, Sr6N”4F8 ⋅ (Me6Tren)2 was formed and structurally characterized. Dissolution in THF led to cluster growth and the larger cluster Sr16N“8F24 ⋅ (THF)12 is structurally characterized. DFT calculations support that hydrodehalogenation of halobenzenes follows a concerted nucleophilic aromatic substitution mechanism (cSNAr).
CRIS-Team Scopus Importer:2021-08-27
Keywords: Alkaline-earth metal; DFT calculation; Hydride; Hydrodehalogenation

Cationic Aluminium Complexes as Catalysts for Imine Hydrogenation - Friedrich, Alexander; Eyselein, Jonathan; Elsen, Holger; Langer, Jens; Pahl, Jürgen; Wiesinger, Michael; Harder, Sjoerd (Chemistry - A European Journal, 2021)
Strongly Lewis acidic cationic aluminium complexes, stabilized by β–diketiminate (BDI) ligands and free of Lewis bases, have been prepared as their B(C6F5)4− salts and were investigated for catalytic activity in imine hydrogenation. The backbone (R1) and N (R2) substituents on the R1,R2BDI ligand (R1,R2BDI=HC[C(R1)N(R2)]2) influence sterics and Lewis acidity. Ligand bulk increases along the row Me,DIPPBDI<Me,DIPePBDI≈tBu,DIPPBDI<tBu,DIPePBDI; DIPP=2,6-C(H)Me2-phenyl, DIPeP=2,6-C(H)Et2-phenyl. The Gutmann-Beckett test showed acceptor numbers of: (tBu,DIPPBDI)AlMe+ 85.6, (tBu,DIPePBDI)AlMe+ 85.9, (Me,DIPPBDI)AlMe+ 89.7, (Me,DIPePBDI)AlMe+ 90.8, (Me,DIPPBDI)AlH+ 95.3. Steric and electronic factors need to be balanced for catalytic activity in imine hydrogenation. Open, highly Lewis acidic, cations strongly coordinate imine rendering it inactive as a Frustrated Lewis Pair (FLP). The bulkiest cations do not coordinate imine but its combination is also not an active catalyst. The cation (tBu,DIPPBDI)AlMe+ shows the best catalytic activity for various imines and is also an active catalyst for the Tishchenko reaction of benzaldehyde to benzylbenzoate. DFT calculations on the mechanism of imine hydrogenation catalysed by cationic Al complexes reveal two interconnected catalytic cycles operating in concert. Hydrogen is activated either by FLP reactivity of an Al⋅⋅⋅imine couple or, after formation of significant quantities of amine, by reaction with an Al⋅⋅⋅amine couple. The latter autocatalytic Al⋅⋅⋅amine cycle is energetically favoured.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Aluminium; cations; DFT; hydrogenation; imine

Cationic Heterobimetallic Mg(Zn)/Al(Ga) Combinations for Cooperative C-F Bond Cleavage - Friedrich, Alexander; Eyselein, Jonathan; Langer, Jens; Färber, Christian; Harder, Sjoerd (Angewandte Chemie International Edition, 2021)
Low-valent ((BDI)-B-Me)Al and ((BDI)-B-Me)Ga and highly Lewis acidic cations in [((BDI)-B-tBu)M+.C6H6][(B(C6F5)(4)(-)] (M=Mg or Zn, (BDI)-B-Me=HC[C(Me)N-DIPP](2), (BDI)-B-tBu=HC[C(tBu)N-DIPP](2), DIPP=2,6-diisopropylphenyl) react to heterobimetallic cations [((BDI)-B-tBu)Mg-Al((BDI)-B-Me)(+)], [((BDI)-B-tBu)Mg-Ga((BDI)-B-Me)(+)] and [((BDI)-B-tBu)Zn-Ga((BDI)-B-Me)(+)]. These cations feature long Mg-Al (or Ga) bonds while the Zn-Ga bond is short. The [((BDI)-B-tBu)Zn-Al((BDI)-B-Me)(+)] cation was not formed. Combined AIM and charge calculations suggest that the metal-metal bonds to Zn are considerably more covalent, whereas those to Mg should be described as weak Al-I(or Ga-I)-> Mg2+ donor bonds. Failure to isolate the Zn-Al combination originates from cleavage of the C-F bond in the solvent fluorobenzene to give ((BDI)-B-tBu)ZnPh and ((BDI)-B-Me)AlF+ which is extremely Lewis acidic and was not observed, but ((BDI)-B-Me)Al(F)-(mu-F)-(F)Al((BDI)-B-Me)(+) was verified by X-ray diffraction. DFT calculations show that the remarkably facile C-F bond cleavage follows a dearomatization/rearomatization route.
CRIS-Team WoS Importer:2021-06-25

Combining Low-Valent AlI and SnII Metal Centers for Small Molecule Activation - Löwl, Tristan; Maurer, Johannes; Roig, Nil; Mai, Jonathan; Langer, Jens; Alonso, Mercedes; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2025)
Reaction of the AlI complex (DIPPBDI-H)AlˉK+ with the SnII complex (DIPPBDI)SnCl gave (DIPPBDI-H)AlSn(DIPPBDI) (1); DIPPBDI = HC[C(Me)N(DIPP)]2, DIPP = 2,6-diisopropylphenyl, DIPPBDI-H = H2C=C(N-DIPP)-C(H)=C(Me)-N-DIPP. The crystal structure shows an asymmetric complex with a planar but strongly distorted trigonal coordination geometry at Al and trigonal pyramidal coordination at Sn. This geometry supports a donor-acceptor bonding model in which (DIPPBDI-H)Alˉ donates an sp2 electron pair in an empty p-orbital of (DIPPBDI)Sn+. Computational analysis supports polar covalent Al-Sn bonding which based on EDA-NOCV analysis is best described as the interaction of two neutral open shell AlII/SnI fragments: (DIPPBDI-H)Al● / (DIPPBDI)Sn●. Effective-Oxidation-State (EOS) analysis assigns the oxidation states AlI/SnII supporting the description of the bond as a (DIPPBDI-H)Alˉ → (DIPPBDI)Sn+ donor-acceptor interaction. However, the rather low reliability index of only 58.1% suggests that this description is not fully representative for the electronic situation. Reacting the electron rich, polarized Ald+-Sndˉ bond with alkynes gave cis-insertion, indicating a concerted reaction with a four-membered ring transition state. Reaction with CO2 selectively gave Al-O2C-Sn insertion, supporting the nucleophilic character of the electron rich Sn centre. The dianionic (DIPPBDI-H)2ˉ ligand is in these reactions not inert and reacts as C-centered nucleophile with alkyne or CO2 resulting in dianionic tridentate ligands.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Aluminium; DFT; Low-valent; metal-metal bonding; tin

Comparison of Magnesium and Zinc in Cationic π-Arene and Halobenzene Complexes - Friedrich, Alexander; Eyselein, Jonathan; Langer, Jens; Harder, Sjoerd (Organometallics, 2021)
The reaction of (tBuBDI)ZnEt with [Ph3C+][B(C6F5)4-] yielded the cation (tBuBDI)Zn+ (tBuBDI = CH[C(tBu)N-DIPP]2, DIPP = 2,6-diisopropylphenyl). The cation is sterically too shielded to interact with the ion B(C6F5)4- but forms complexes with arenes (benzene, toluene, m-xylene) or halobenzenes (PhX: X = F, Cl, Br, I). Crystal structures of these complexes are compared with those of the corresponding Mg complexes. Although Mg2+ and Zn2+ are of equal size, the Zn···arene and Zn···XPh contacts are generally 0.1-0.2 Å shorter than comparable contacts to (tBuBDI)Mg+. This originates from differences in bond character: bonding to Mg has a more electrostatic nature. A major difference between Mg and Zn is observed for PhF complexation. While the hard Mg2+ cation prefers Mg···FPh bonding, the softer Zn2+ shows a Zn···( π)PhF interaction. Heavier halobenzenes with softer halogens (Cl, Br, I) show Zn···XPh bonding. DFT calculations on (tBuBDI)Zn+···XPh (X = F, Cl, Br, I) show decreasing Zn···X-Ph angles from PhF to PhI on account of the increase in the halogen's σ-hole. Zn···XPh interactions result in C-X bond lengthening, but C-X bond activation is less pronounced than in corresponding Mg···XPh complexes. Weak (tBuBDI)Zn+···XPh bonding could not be detected in solution but is believed to play a role in the functionalization of organohalides by Zn reagents.
CRIS-Team Scopus Importer:2021-03-26

Dinitrogen complexation and reduction at low-valent calcium - Rösch, Bastian; Gentner, Thomas; Langer, Jens; Färber, Christian; Eyselein, Jonathan; Zhao, L.; Ding, C.; Frenking, G.; Harder, Sjoerd (Science, 2021)
Here we report that attempted preparation of low-valent CaI complexes in the form of LCa-CaL (where L is a bulky b-diketiminate ligand) under dinitrogen (N2) atmosphere led to isolation of LCa(N2)CaL, which was characterized crystallographically. The N22- anion in this complex reacted in most cases as a very potent two-electron donor. Therefore, LCa(N2)CaL acts as a synthon for the low-valent CaI complex LCa-CaL, which was the target of our studies. The N22- anion could also be protonated to diazene (N2H2) that disproportionated to hydrazine and N2. The role of Ca d orbitals for N2 activation is discussed.
CRIS-Team Scopus Importer:2021-03-26

Diverse Reactivity of a Ca(I) Synthon - Mai, Jonathan; Rösch, Bastian; Langer, Jens; Grams, Samuel; Morasch, Michael; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2023)
Low-valent MgI complexes like (BDI)Mg−Mg(BDI) have found wide-spread application as specialty reducing agents (BDI=β-diketiminate). Also their redox reactivity was extensively investigated. In contrast, attempts to isolate similar CaI complexes led to reduction of the aromatic solvents or N2. Complex (DIPePBDI)Ca(μ6,μ6-C6H6)Ca(DIPePBDI) (VIII) should be regarded a CaII complex with a bridging C6H62− dianion (DIPePBDI=HC[C(Me)N-DIPeP]2, DIPeP=2,6-C(H)Et2-phenyl). It can react as a CaI synthon by releasing benzene and two electrons. Herein we describe the reactivity of VIII with benzene, biphenyl, naphthalene, anthracene, COT, Ph3SiCl, PhSiH3, a (BDI)AlI2 complex, H2, PhX (X=F, Cl, Br, I), tBuOH and tBuCH2I. The C6H62− dianion in VIII can react as a 2e− source, a nucleophile or a Brønsted base. In some cases radical reactivity cannot be excluded. Crystal structures of (DIPePBDI)Ca(μ8,μ8-COT)Ca(DIPePBDI) (1) and [(DIPePBDI)CaX ⋅ (THF)]2 (X=F, Cl, Br, I) (2–5) are described.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Calcium; low-valent compounds; reactivity; reduction; β-diketiminate

Heterobimetallic alkaline earth metal–metal bonding - Mai, Jonathan; Maurer, Johannes; Langer, Jens; Harder, Sjoerd (Nature Synthesis, 2023)
Low-oxidation-state complexes of type (BDI)Mg–Mg(BDI) (BDI, β-diketiminate) show broad reactivity, finding application as soluble, universal reducing agents, enriching the field of early main group metal chemistry. Attempts to isolate similar, but considerably more reactive, Ca–Ca bound complexes have so far failed. As the metal–metal bond strength descending group 2 rapidly decreases, BDI complexes of the heavier AeI (alkaline earth) ions (Ae = Ca, Sr, Ba) probably exist as (BDI)Ae· radicals of untamed reactivity. Here we describe a facile method to prepare stable but highly reactive complexes with heterobimetallic Mg–Ae bonds. Mixing [(BDI)MgˉNa+]2 and [Ae(NR2)2]2 dimers led to anion–cation exchange and exclusive formation of mixed species: (BDI)MgˉNa+/Ae(NR2)2 (Ae = Ca, Sr, Ba; R = SiMe3). Crystal structures feature examples of Mg–Ca and Mg–Sr bonding with formal oxidation states of Mg0–AeII. Best described as polarized Mgδˉ–Aeδ+ bonds, these complexes show potential as alkane-soluble reductants for bond activation, which readily react with benzene by C–H bond cleavage and are oxidized to discrete complexes with N2O. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-12-15

Heterometallic Mg−Ba Hydride Clusters in Hydrogenation Catalysis - Wiesinger, Michael; Knüpfer, Christian; Elsen, Holger; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (ChemCatChem, 2021)
Reaction of a MgN“2/BaN”2 mixture (N“=N(SiMe3)2) with PhSiH3 gave three unique heterometallic Mg/Ba hydride clusters: Mg5Ba4H11N”7 ⋅ (benzene)2 (1), Mg4Ba7H13N“9 ⋅ (toluene)2 (2) and Mg7Ba12H26N”12 (3). Product formation is controlled by the Mg/Ba ratio and temperature. Crystal structures are described. While 3 is fully insoluble, clusters 1 and 2 retain their structures in aromatic solvents. DFT calculations and AIM analyses indicate highly ionic bonding with Mg−H and Ba−H bond paths. Also unusual H−⋅⋅⋅H− bond paths are observed. Catalytic hydrogenation with MgN“2, BaN”2 and the mixture MgN“2/BaN”2 has been studied. Whereas MgN“2 is only active in imine hydrogenation, alkene and alkyne hydrogenation needs the presence of Ba. The catalytic activity of the MgN”2/BaN“2 mixture lies in general between that of its individual components and strong cooperative effects are not evident.
CRIS-Team Scopus Importer:2021-09-17
Keywords: alkaline earth metal; catalysis; DFT calculations; heterometallic; hydride

Highly Active Superbulky Alkaline Earth Metal Amide Catalysts for Hydrogenation of Challenging Alkenes and Aromatic Rings - Martin, Johannes; Knüpfer, Christian; Eyselein, Jonathan; Färber, Christian; Grams, Samuel; Langer, Jens; Thum, Katharina; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Two series of bulky alkaline earth (Ae) metal amide complexes have been prepared: Ae[N(TRIP)2]2 (1-Ae) and Ae[N(TRIP)(DIPP)]2 (2-Ae) (Ae=Mg, Ca, Sr, Ba; TRIP=SiiPr3, DIPP=2,6-diisopropylphenyl). While monomeric 1-Ca was already known, the new complexes have been structurally characterized. Monomers 1-Ae are highly linear while the monomers 2-Ae are slightly bent. The bulkier amide complexes 1-Ae are by far the most active catalysts in alkene hydrogenation with activities increasing from Mg to Ba. Catalyst 1-Ba can reduce internal alkenes like cyclohexene or 3-hexene and highly challenging substrates like 1-Me-cyclohexene or tetraphenylethylene. It is also active in arene hydrogenation reducing anthracene and naphthalene (even when substituted with an alkyl) as well as biphenyl. Benzene could be reduced to cyclohexane but full conversion was not reached. The first step in catalytic hydrogenation is formation of an (amide)AeH species, which can form larger aggregates. Increasing the bulk of the amide ligand decreases aggregate size but it is unclear what the true catalyst(s) is (are). DFT calculations suggest that amide bulk also has a noticeable influence on the thermodynamics for formation of the (amide)AeH species. Complex 1-Ba is currently the most powerful Ae metal hydrogenation catalyst. Due to tremendously increased activities in comparison to those of previously reported catalysts, the substrate scope in hydrogenation catalysis could be extended to challenging multi-substituted unactivated alkenes and even to arenes among which benzene.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Alkaline Earth Metals; Alkenes; Aromatic rings; DFT calculations; Hydrogenation

Hydrogen Isotope Exchange with Superbulky Alkaline Earth Metal Amide Catalysts - Martin, Johannes; Eyselein, Jonathan; Grams, Samuel; Harder, Sjoerd (ACS Catalysis, 2020)
Heavier alkaline earth (Ae) metal amide complexes hydrogen isotope exchange (HIE). The activities for D/H exchange Ae(NR2)(2) (Ae = Ca, Sr, Ba) were found to be highly active catalysts for between C6D6 and H-2 strongly increase with metal size (Ca < Sr < Ba) and with amide bulk: N(SiMe3)(2) < N(DIPP)(SiiPr(3))< N(SiiPr(3))(2), DIPP = 2,6-diisopropylphenyl. At 120 degrees C and pressures of 10-50 bar, no hydrogenation side-products are produced, and TONs of 205 and TOFs of 268, competitive with those for precious metal catalysts, have been achieved. The reverse H/D exchange between C6H6 and D-2 is even faster by a factor 1.5-2. Substrates also include a range of substituted arenes. Alkyl-substituted aromatic rings are preferably deuterated in acidic benzylic positions, and this tendency increases with the number of alkyl-substituents. Although unactivated (sp(3))C-H units could not be deuterated, the (sp(3))Si-H function in primary, secondary, and tertiary alkylsilanes could be converted. Two different pathways for C6H6/D-2 isotope exchange have been evaluated by DFT calculations: (A) a deprotonation/protonation mechanism and (B) direct nucleophilic aromatic substitution. Although the exact nature of the catalyst(s) is unclear, the first step is the conversion of Ae(NR2)(2) with D-2 into R(2)NAeD which can aggregate to larger clusters. Energy profiles with model catalysts (iPr(3)Si)(2)NAeD and [(Me3Si)(2)NAeD](2) (Ae = Ca or Ba) show that the direct nucleophilic aromatic substitution is the most likely mechanism for deuteration of arenes. The key to this unusual reaction is the initial formation of a pi-arene center dot center dot center dot Ae complex which is followed by the generation of an intermediate with a Meisenheimer anion. Heavier Ae metal amide complexes are, despite the lack of partially filled d-orbitals for substrate activation, potent catalysts for HIE.
CRIS-Team WoS Importer:2020-08-14

Large decanuclear calcium and strontium hydride clusters - Martin, Johannes; Eyselein, Jonathan; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Chemical Communications, 2020)
Two large decanuclear hydride clusters of the general formula Ae10H16[N(R)R']4·(PMDTA)2 (Ae = Ca, Sr) were isolated. Both derivatives feature a [Ae10H16]4+ core, consisting of two edge shared metal octahedra with interstitial hydrides, while the other hydrides cap triangular faces.
CRIS-Team Scopus Importer:2020-08-21

Lewis Acidic Cationic Strontium and Barium Complexes - Thum, Katharina; Martin, Johannes; Elsen, Holger; Eyselein, Jonathan; Stiegler, Lisa; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2021)
Lewis acidic (BDI)Ae+ cations of the heavier metals Sr and Ba, which are not stabilized by polar solvents, have been obtained by double deprotonation of (BDI)H2+ with either SrN’’2 or BaN’’2; BDI = HC[C(Me)N(DIPP)]2, DIPP = 2,6-diisopropylphenyl, Ae = alkaline earth, N’’ = N(SiMe3)2. Due to clathrate formation [(BDI)Ae+][B(C6F5)4−] could not be crystallized, but pyrene addition gave crystalline [(BDI)Ae+ ⋅ pyrene][B(C6F5)4−] which was structurally characterized for Ae = Mg, Ca, Sr, Ba. (R2N)Ae+ cations of the heavier metals Sr and Ba were obtained by reaction of Ae(NR2)2 with [Ph3C+][B(C6F5)4−] or [PhNMe2H+][B(C6F5)4−]. Following complexes were structurally characterized: [N’’Ba+ ⋅ (tol)2][B(C6F5)4−], [N*Sr+ ⋅ PhNMe2][B(C6F5)4−], [N*Ba+ ⋅ tol][B(C6F5)4−] and [N*Ba+ ⋅ C6H6][B(C6F5)4−]; tol = toluene and N* = N(SiiPr3)2. DFT calculations show that Sr⋅⋅⋅PhNMe2 coordination is preferred over Sr⋅⋅⋅toluene bonding. The (R2N)Ae+ cations can be used as Brønsted bases (reaction with (BDI)H gave (BDI)Ae+) and may be useful precursors for a variety of Lewis base-free RAe+ cations. DFT calculations, limited to monomeric model systems including B(C6F5)4− (ωB97XD/def2tzvpp//ωB97XD/def2svp), show that there is negligible electron transfer from the pyrene or toluene ligands to the Ae2+ cation. Electrostatic attraction originates from charge-induced polarization of the (Formula presented.) -electron density in the toluene and pyrene ligands.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Ab initio calculations; Arene coordination; Barium; Cations; Strontium

Magnesium-halobenzene bonding: mapping the halogen sigma-hole with a Lewis-acidic complex - Friedrich, Alexander; Pahl, Jürgen; Eyselein, Jonathan; Langer, Jens; van Eikema Hommes, Nico; Görling, Andreas; Harder, Sjoerd (Chemical Science, 2021)
Complexes of the Lewis base-free cations (MeBDI)Mg+and (tBuBDI)Mg+with Ph-X ligands (X = F, Cl, Br, I) have been studied (MeBDI = HC[C(Me)N-DIPP]2andtBuBDI = HC[C(tBu)N-DIPP]2; DIPP = 2,6-diisopropylphenyl). For the smaller β-diketiminate ligand (MeBDI) only complexes with PhF could be isolated. Heavier Ph-X ligands could not compete with bonding of Mg to the weakly coordinating anion B(C6F5)4−. For the cations with the bulkiertBuBDI ligand, the full series of halobenzene complexes was structurally characterized. Crystal structures show that the Mg⋯X-Ph angle strongly decreases with the size of X: F 139.1°, Cl 101.4°, Br 97.7°, I 95.1°. This trend, which is supported by DFT calculations, can be explained with the σ-hole which increases from F to I. Charge calculation and Atoms-In-Molecules analyses show that Mg⋯F-Ph bonding originates from electrostatic attraction between Mg2+and the very polar Cδ+-Fδ−bond. For the heavier halobenzenes, polarization of the halogen atom becomes increasingly important (Cl < Br < I). Complexation with Mg leads in all cases to significant Ph-X bond activation and elongation. This unusual coordination of halogenated species to early main group metals is therefore relevant to C-X bond breaking.
CRIS-Team Scopus Importer:2021-03-19

Metallic Barium: A Versatile and Efficient Hydrogenation Catalyst - Stegner, Philipp; Färber, Christian; Zenneck, Ulrich; Knüpfer, Christian; Eyselein, Jonathan; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Ba metal was activated by evaporation and cocondensation with heptane. This black powder is a highly active hydrogenation catalyst for the reduction of a variety of unactivated (non-conjugated) mono-, di- and tri-substituted alkenes, tetraphenylethylene, benzene, a number of polycyclic aromatic hydrocarbons, aldimines, ketimines and various pyridines. The performance of metallic Ba in hydrogenation catalysis tops that of the hitherto most active molecular group 2 metal catalysts. Depending on the substrate, two different catalytic cycles are proposed. A: a classical metal hydride cycle and B: the Ba metal cycle. The latter is proposed for substrates that are easily reduced by Ba0, that is, conjugated alkenes, alkynes, annulated rings, imines and pyridines. In addition, a mechanism in which Ba0 and BaH2 are both essential is discussed. DFT calculations on benzene hydrogenation with a simple model system (Ba/BaH2) confirm that the presence of metallic Ba has an accelerating effect.
CRIS-Team Scopus Importer:2020-12-25
Keywords: alkaline earth metals; barium; hydride; hydrogenation catalysis; metal activation

Mg-Mg bond polarization induced by a superbulky β-diketiminate ligand - Rösch, Bastian; Gentner, Thomas; Eyselein, Jonathan; Friedrich, Alexander; Langer, Jens; Harder, Sjoerd (Chemical Communications, 2020)
The bulk of a recently reported superbulky β-diketiminate ligand was further increased by introducing tBu substituents in the ligand backbone. Attempts to isolate free Mg radicals with this extremely bulky ligand failed. Instead, a dinuclear Mg(i) complex with one chelating and one monodentate β-diketiminate ligand was isolated. Asymmetry in metal coordination results in a polarized Mg-Mg bond.
CRIS-Team Scopus Importer:2020-10-09

On the existence of low-valent magnesium-calcium complexes - Mai, Jonathan; Rösch, Bastian; Patel, Neha; Langer, Jens; Harder, Sjoerd (Chemical Science, 2023)
DFT-Calculations predict that a low-valent complex (BDI)Mg-Ca(BDI) with bulky beta-diketiminate (BDI) ligands is thermodynamically stable. It was attempted to isolate such a complex by salt-metathesis between [((BDI)-B-DIPeP*) Mg-Na+](2) and [((BDI)-B-DIPeP)CaI](2) ((BDI)-B-DIPeP = HC[C(Me)N-DIPeP](2); (BDI)-B-DIPeP* = HC [C(tBu)N-DIPeP](2); DIPeP = 2,6-CH(Et)(2)-phenyl). Whereas in alkane solvents no reaction was observed, salt-metathesis in C6H6 led to immediate C-H activation of benzene to give ((BDI)-B-DIPeP*) MgPh and ((BDI)-B-DIPeP) CaH, the latter crystallizing as a THF-solvated dimer [((BDI)-B-DIPeP) CaHTHF](2). Calculations suggest reduction and insertion of benzene in the Mg-Ca bond. The activation enthalpy for the subsequent decomposition of C(6)H(6)2(-) into Ph- and H- is only 14.4 kcal mol(-1). Repeating this reaction in the presence of naphthalene or anthracene led to heterobimetallic complexes in which naphthalene(2-) or anthracene(2-) anions are sandwiched between ((BDI)-B-DIPeP*)Mg+ and ((BDI)-B-DIPeP)Ca+ cations. These complexes slowly decompose to their homometallic counterparts and further decomposition products. Complexes in which naphthalene(2-) or anthracene(2-) anions are sandwiched between two ((BDI)-B-DIPeP)Ca+ cations were isolated. The low-valent complex (BDI)-B-(DIPeP*)Mg-Ca((BDI)-B-DIPeP) could not be isolated due to its high reactivity. There is, however, strong evidence that this heterobimetallic compound is a fleeting intermediate.
CRIS-Team WoS Importer:2023-05-26

Redox-active inverse crowns for small molecule activation - Maurer, Johannes; Klerner, Lukas; Mai, Jonathan; Stecher, Hannah; Thum, Stefan; Morasch, Michael; Langer, Jens; Harder, Sjoerd (Nature Chemistry, 2025)
Cyclic crown ethers bind metal cations to form host–guest complexes. Lesser-known inverse crowns are rings of metal cations that encapsulate anionic entities, enabling multiple deprotonation reactions, often with unusual selectivity. Self-assembly of a cycle of metal cations around the multiply charged carbanion during the deprotonation reaction is the driving force for this reactivity. Here we report the synthesis of a pre-assembled inverse crown featuring Na+ cations and a redox-active Mg0 centre. Reduction of N2O followed by N2 release and subsequent encapsulation of O2− demonstrates its reduce-and-capture functionality. Calculations reveal that this essentially barrier-free process involves a rare N2O2− dianion, embedded in the metalla-cycle. The inverse crown can adapt itself for binding larger anions like N2O22− through a self-reorganization process involving ring expansion. The redox-active inverse crown combines the advantages of a strong reducing agent with anion stabilizing properties provided by the ring of metal cations, leading to high reactivity and selectivity. (Figure presented.)
CRIS-Team Scopus Importer:2025-02-28

Reductive cyclotrimerization of CO and isonitriles with a highly reactive CaI synthon - Thum, Stefan; Mai, Jonathan; Schmidt, Marcel; Langer, Jens; Harder, Sjoerd (Chemical Science, 2025)
Whereas the small molecule activation with β-diketiminate (BDI)MgI complexes of type (BDI)Mg-Mg(BDI) is extensively investigated, lack of similar CaI reagents prevents studies on CaI reactivity. Herein, we report on small molecule activation with dinitrogen complexes of type (BDI)Ca(N2)Ca(BDI) which acts as CaI synthon by release of N2 and two electrons. Reaction of [(BDI*)Ca(THP)]2(N2) with CO led to formation of a deltate product with the cyclic C3O32− dianion (1); BDI* = HC[C(Me)N(DIPeP)]2 (DIPeP = 2,6-(Et2CH)-phenyl) and THP = tetrahydropyran. Reaction with the isonitrile CyN 00000000000000000 00000000000000000 00000000000000000 01111111111111110 00000000000000000 01111111111111110 00000000000000000 01111111111111110 00000000000000000 00000000000000000 00000000000000000 C gave as the major product a complex with the triimino deltate C3(NCy)32− dianion (2) which is unstable in solution. Isolation of the side-product (BDI*)2Ca·(CN-Cy) (3) indicates dynamic ligand exchange and Schlenk equilibria. Variation of the isonitrile reagent led to isolation of (BDI*)2Ca·(CN-R) (4: R = xylyl, 5: R = tBu). Crystal structures and NMR studies in solution are discussed for complexes 1-5. We also report an extensive DFT study on the reductive trimerization of MeN C with this CaI synthon. The key intermediate (BDI)Ca(MeNC)Ca(BDI) contains dianionic MeNC2−. Contrary to expectation, C-C coupling does not proceed by nucleophilic attack at a second MeNC reagent. Electron transfer results in two bridging MeNC˙− radical anions. This rare singlet diradicaloid reacts further by radical coupling to [MeNC-CNMe]2−. Differences with MgI reactivity are discussed.
CRIS-Team Scopus Importer:2025-06-20

Retro-Diels-Alder decomposition of norbornadiene mediated by a cationic magnesium complex - Thum, Katharina; Pahl, Jürgen; Eyselein, Jonathan; Elsen, Holger; Langer, Jens; Harder, Sjoerd (Chemical Communications, 2021)
First evidence for the coordination of norbornadiene (nbd) and dicyclopentadiene (dcpd) with the main group metal Mg is provided by the crystal structures of adducts with cationic beta-diketiminate (BDI) Mg complexes. While the dcpd complex is thermally stable, [(BDI)Mg+center dot nbd][B(C6F5)(4)(-)] shows slow room temperature retro-Diels-Alder decomposition to give a complex with the cation (BDI)Mg(C5H5)Mg(BDI)(+).
CRIS-Team WoS Importer:2021-05-28

s-Block metal complexes of superbulky (tBu3Si)2N-: a new weakly coordinating anion? - Knüpfer, Christian; Klerner, Lukas; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (Chemical Science, 2024)
Sterically hindered amide anions have found widespread application as deprotonation agents or as ligands to stabilize metals in unusual coordination geometries or oxidation states. The use of bulky amides has also been advantageous in catalyst design. Herein we present s-block metal chemistry with one of the bulkiest known amide ligands: (tBu3Si)2N- (abbreviated: tBuN-). The parent amine (tBuNH), introduced earlier by Wiberg, is extremely resistant to deprotonation (even with nBuLi/KOtBu superbases) but can be deprotonated slowly with a blue Cs+/e- electride formed by addition of Cs0 to THF. (tBuN)Cs crystallized as a separated ion-pair, even without cocrystallized solvent. As salt-metathesis reactions with (tBuN)Cs are sluggish and incomplete, it has only limited use as an amide transfer reagent. However, ball-milling with LiI led to quantitative formation of (tBuN)Li and CsI. Structural characterization shows that (tBuN)Li is a monomeric contact ion-pair with a relatively short N-Li bond, an unusual T-shaped coordination geometry around N and extremely short Li?Me anagostic interactions. Crystal structures are compared with Li and Cs complexes of less bulky amide ligands (iPr3Si)2N- (iPrN-) and (Me3Si)2N- (MeN-). DFT calculations show trends in the geometries and electron distributions of amide ligands of increasing steric bulk (MeN- < iPrN- < tBuN-) and confirm that tBuN- is a rare example of a halogen-free weakly coordinating anion.
CRIS-Team Scopus Importer:2024-03-15

Strongly reducing magnesium(0) complexes - Rösch, Bastian; Gentner, Thomas; Eyselein, Jonathan; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Nature, 2021)
A complex of a metal in its zero oxidation state can be considered a stabilized, but highly reactive, form of a single metal atom. Such complexes are common for the more noble transition metals. Although rare examples are known for electronegative late-main-group p-block metals or semimetals1-6, it is a challenge to isolate early-main-group s-block metals in their zero oxidation state7-11. This is directly related to their very low electronegativity and strong tendency to oxidize. Here we present examples of zero-oxidation-state magnesium (that is, magnesium(0)) complexes that are stabilized by superbulky, monoanionic, β-diketiminate ligands. Whereas the reactivity of an organomagnesium compound is typically defined by the nucleophilicity of its organic groups and the electrophilicity of Mg2+ cations, the Mg0 complexes reported here feature electron-rich Mg centres that are nucleophilic and strongly reducing. The latter property is exemplified by the ability to reduce Na+ to Na0. We also present a complex with a linear Mg3 core that formally could be described as a MgI-Mg0-MgI unit. Such multinuclear mixed-valence Mgn clusters are discussed as fleeting intermediates during the early stages of Grignard reagent formation. Their remarkably strong reducing power implies a rich reactivity and application as specialized reducing agents.
CRIS-Team Scopus Importer:2021-05-14

Synthesis, Structure, and Reactivity of a Superbulky Low-Valent β-Diketiminate Al(I) Complex - Grams, Samuel; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (Organometallics, 2022)
Low-valent β-diketiminate Al(I) complexes are generally synthesized in low yields (<20%). This is due to an intermolecular decomposition reaction. A new β-diketiminate Al(I) complex with a very bulky β-diketiminate ligand DIPePBDI was obtained in a high yield (81%) and the raw product was found to be essentially pure (DIPePBDI = HC[C(Me)N(DIPeP)]2; DIPeP = 2,6-C(H)Et2-phenyl). The crystal structure of (DIPePBDI)Al shows a monomeric complex. The reaction of (DIPePBDI)Al with AlBr3 gave (DIPePBDI)AlBr2 and Al(0). The reaction of (DIPePBDI)Al with KCH(SiMe3)2 led to deprotonation of a backbone Me group and formation of a K aluminyl complex. A minor side-product in which the BDI ligand was cleaved is also described. The very high yield of (DIPePBDI)Al makes it a welcome addition to the family of β-diketiminate Al(I) complexes.
CRIS-Team Scopus Importer:2022-10-28